Uttar Pradesh : the road ahead - Ramakrishnan, Venkitesh; Observer Research Foundation (New Delhi Academic Foundation in association with Observer Research Foundation, 2009)
Papers presented at the seminar on the theme "Uttar Pradesh : the road ahead", held at New Delhi during 23-24 May 2008 moderated by the Observer Research Foundation on socio-political and economic development in Uttar Pradesh.
Keywords: Regionalism -- India -- Uttar Pradesh; Uttar Pradesh (India) -- Politics and government -- 21st century -- Congresses; Uttar Pradesh (India) -- Social policy -- Congresses; Uttar Pradesh (India) -- Economic policy -- Congresses